Development of an E-Book on Basic Hair-Cutting Courses for Cosmetology Education Students - Sari, Dian Maya; Fauzani, Asrah Reski (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The minimal availability of learning media about basic hair cutting and the lack of maximum student learning outcomes are the basis for developing e-books. This research aims to develop e-book media in basic hair-cutting development courses for cosmetology education students. The development model used is the ADDIE model. The data collection technique uses a questionnaire. The result of the media needs analysis carried out on students was 96% and the lecturer was 98%, which indicates that media are needed for learning basic hair-cutting. Material expert validation’s average percentage was 88.20%, which is in the very good category. Media expert validation average result was 93.88%, which is in the very good category. The small-scale trial was 92% with the very good category. The medium group trial indicated 92.88% with the very good category. In addition, the large group trial was 94.12% with the very good category. Therefore, e-book media is suitable for use as a learning medium in basic hair-cutting courses. The implication of developing this E-Book is that students can practice and repeat basic hair-cutting independently, and can attract students' interest in the learning process.